Design, synthesis and evaluate of imidazole, triazine and metastable oxazolone derivatives as chemosensor for detecting metals - Ayman M. Algohary; Mona H. Alhalafi (Journal of Saudi Chemical Society, 2022)
In the current work, a novel series of substituted imidazole, triazine and metastable Oxazolone derivatives were synthesized. The performance of 4-arylideneoxazol-5(4H)-one (2a-c) towards amoniuma acetate, hydrazine hydrate, phenyhydrazine and primary amines has been discussed. DFT bases and calculations of HUMO, LUMO were used to predict the ability of binding between synthesized compound and cations. All the synthesized compounds were assessed as chemosensors for detection metals ions. Colorimetric investigation confirmed and showed high-selectivity and specificity of compounds 5b and 5c to detect cobalt ion, and copper ion respectively, so compounds 5b and 5c can be directed as a chemosensor for optical detection of Co2+and Cu2+ respectively. On the other hand, new organic chemosensor were established by, IR, 1H NMR, 13C NMR ms spectroscopy and elemental analysis.